Subarachnoid Hemorrhage Due to Rupture of an Intracavernous Carotid Artery Aneurysm Coexisting with a Prolactinoma under Cabergoline Treatment - Akutsu, Nobuyuki; Hosoda, Kohkichi; Ohta, Kohei; Tanaka, Hirotomo; Taniguchi, Masaaki; Kohmura, Eiji (Journal of Neurological Surgery Reports, 2014)
We report an unusual case of subarachnoid hemorrhage caused by intraoperative rupture of an intracavernous carotid artery aneurysm coexisting with a prolactinoma. A 58-year-old man presenting with diplopia was found to have a left intracavernous carotid artery aneurysm encased by a suprasellar tumor on magnetic resonance imaging. His serum prolactin level was 5036 ng/mL. Proximal ligation of the left internal carotid artery with a superficial temporal artery to middle cerebral artery anastomosis was scheduled. Because the patient's diplopia had deteriorated, we started him on cabergoline at a dose of 0.25 mg once a week. One month after administration of cabergoline, the diplopia was improved to some extent and serum prolactin was decreased to 290 ng/ml. Six weeks after starting the cabergoline, the patient underwent a left frontotemporal craniotomy to treat the aneurysm. When the dura mater was opened, abnormal brain swelling and obvious subarachnoid hemorrhage were observed. Postoperative computed tomography demonstrated a thick subarachnoid hemorrhage. This case suggests that medical therapy for a pituitary adenoma should be started after treatment for a coexisting intracavernous aneurysm is completed.
Keywords: intracavernous aneurysm; subarachnoid hemorrhage; prolactinoma; cabergoline